Arbuscular mycorrhizal fungi can improve the growth of aromatic plants and prevent soil erosion after forest fires - Duarte, Beatriz (2014)
Forest fires are regarded as one of the major environmental problems in Portugal. Among their negative impacts is loss of green area and soil structure damage, which increase soil erodibility. Adequate soil structure is essential to support plant and animal life and to moderate environmental quality with particular emphasis on soil carbon sequestration and water quality (Certini, 2005). After a forest fire the ecosystem has the capacity to recover through ecological succession. This is, however, a slow process and there is the need for human intervention in order to mitigate the negative impacts of forest fires. Aromatic plants, such as rosemary, are among the first to grow in post-fire Mediterranean forest ecosystems (Luis et al., 2006). This together with their commercial value makes these plants attractive candidates to be used in the first stages of restoration of burned forest soils. Arbuscular mycorrhizal fungi (AMF) are a group of soil microorganisms that forms mutualistic symbioses that can benefit plants by improving the uptake of mineral nutrients, mineralising organic nutrients and conferring drought resistance (Oliveira et al., 2005).AMF have also the capacity to promote soil aggregation by several mechanisms including the release of soil binding agents.